Cretaceous oceanic anoxic events and radially elongated chambered planktonic foraminifera: paleoecological and paleoceanographic implications. - COCCIONI R; MARSILI A.; LUCIANI, Valeria (2006)
Chamber elongation is a recurring morphological character in Cretaceous and Cenozoic planktonic foraminiferal evolution suggesting that the clavate body-plan takes advantage through particular environmental conditions. Cretaceous planktonic foraminifera bearing radially elongated chambers become repeatedly a consistent component of assemblages in correspondence with the deposition of remarkable organic layers that record the effects of oceanic anoxic events (OAEs). Due to this apparent correspondence, chamber elongation has been recently interpreted as an adaptation to low oxygen levels in the upper water column. The paleoceanographic significance of planktonic foraminifera with radially elongated chambers remains however unclear. We investigated in great detail the distribution and abundance of elongated chambered planktonic foraminifera in an interval of about 40 myr across the Cretaceous OAEs in different well-dated sections. The increased abundance of planktonic foraminifera with elongated chambers can be a markedly evident feature across the Faraoni, the Selli and the Bonarelli OAEs. However each event shows its own peculiarities. Remarkably, the first radiation of the Cretaceous elongated chambered morphotypes just predates the latest Hauterivian Faraoni Event. The Selli Event records the greatest diversification (number of species) of the group bearing elongated chambers. However, this was a period of great diversification in the planktonic foraminifera. This evidence may suggest that radiation of these forms was driven by more than upper water column anoxia per se (e.g., increased upper water column stratification, greater productivity, and/or greater seasonality). The Albian OAE1b, OAE1c, and OAE1d display the lowest abundance and diversity of this group. Conversely, according to the available data, the first appearances of the species Muricohedbergella simplex and of the genus Schackoina occur close to the OAE1b and OAE1d, respectively. In the Italian record, the relative abundance of radially ...